2016
DOI: 10.1249/jsr.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nutritional Supplements in Sports Concussion Treatment

Abstract: There has been considerable research conducted in regard to the prevention and treatment of concussions. Numerous supplements and vitamins are being used throughout the country to help patients recover from concussions; however, to date, there are no completed human-based studies specifically examining supplement and vitamin use for the treatment or prevention of concussions. This article examines the most current evidence regarding supplements and vitamins for the treatment and prevention of concussions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Furthermore, given the impact of concussion there has been interest in supplements that can mitigate its affects. Omega-3 fatty acids, curcumin and resveratrol have been shown to have protective effects 5 and supplementation of DHA may offset the number of concussions experienced 63 and control the inflammation from acute football exercise 64 . Hydration is also critical to both health and performanceespecially when practices can occur in padded equipment in extreme environments.…”
Section: Nutrition Requirements and Considerations For Afmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, given the impact of concussion there has been interest in supplements that can mitigate its affects. Omega-3 fatty acids, curcumin and resveratrol have been shown to have protective effects 5 and supplementation of DHA may offset the number of concussions experienced 63 and control the inflammation from acute football exercise 64 . Hydration is also critical to both health and performanceespecially when practices can occur in padded equipment in extreme environments.…”
Section: Nutrition Requirements and Considerations For Afmentioning
confidence: 99%
“…Scientific studies on collegiate AF have grown exponentially since the first paper in 1969, leading to various avenues of scientific development in key areas from this time to the present day. These include injury prevention 3,4 , concussion 5 , return to play injury characteristics 6,7 , analysis of strength and conditioning [8][9][10][11] , overall health 12 and wellbeing and most recently the objective quantification of training and games [13][14][15] .…”
Section: Conceptual Introductionmentioning
confidence: 99%
“…In the world of sport, athletes and coaches emphasize the importance of a healthy and balanced diet both for the improvement of health and performance. Diet, training skills and functional demands directly influence sports competition, especially at high levels (Ashbaugh A., McGrew C, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The nutrition of the sportsman must ensure the contribution of energy, in the form of calories and promoteand maintain a high level of psychophysical wellbeing (Mazzeo, 2016;Chulvi-Medrano et al, 2019). There are variations in energy expenditure depending on the type of sports activity considered and practiced (Hawley et al, 1995) but also in relation to the registry and morphological variables (Illiano et al 2017;Montesano et al, 2013); it is important to draw up a training protocol with a proper nutritional structure associated, where necessary, with a correct integration of vitamins and / or essential fatty acids (Ashbaugh., McGrew., 2016;Mazzeo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disturbances, which can occur shortly after a concussion, can be treated with melatonin in the acute setting. 47 Other medications have been trialed outside of the acute setting for those patients with persistent post-concussive syndrome, including gabapentin, topiramate, and amitriptyline. While a complete discussion of their efficacy is beyond the scope of this review, amitriptyline has been shown to be most effective for post-concussive headaches.…”
Section: Management: Medicationsmentioning
confidence: 99%